Positive electrode current collector, secondary battery and electric equipment

By using porous aluminum foil current collector and combining copper-aluminum alloy materials, the problem of insufficient bonding force between the positive electrode current collector and the active material material is solved, and the electrical and safety performance of the battery is significantly improved.

CN119812352APending Publication Date: 2025-04-11SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411992402.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the bonding force between the positive electrode current collector and the active material material is insufficient, resulting in cracking of the current collector when the coating weight is too high or the temperature is too high, causing a micro-short circuit, affecting the charging and discharging performance and safety performance of the battery.

Method used

The aluminum foil current collector with a porous structure is used, and its porous layer contains a copper-aluminum alloy with an average specific surface area of ​​8 to 15 m2/g, providing more adhesion area, improving the bonding force between the positive electrode active material and the current collector, and improving deformation resistance and thermal conductivity through the copper-aluminum alloy.

Benefits of technology

It significantly improves the peeling force of the positive electrode active material, enhances its stability on the foil surface, avoids powder loss, improves the electrical and safety performance of the battery, and slows down thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812352A_ABST
    Figure CN119812352A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of current collector preparation, and particularly relates to a positive current collector, a secondary battery and electric equipment. The positive current collector comprises a body layer, wherein the body layer is made of aluminum; the porous layer is provided with a plurality of pore structures and is arranged on at least one surface of the body layer; the porous layer comprises a copper-aluminum alloy, and the average specific surface area of the porous layer is 8-15 m < 2 > / g. According to the positive electrode current collector with the surface porous structure, the porous layer contains the copper-aluminum alloy, the average specific surface area is 8-15 m < 2 > / g, more attachment area can be provided, compared with traditional smooth aluminum foil, the binding capacity of the positive electrode current collector and a positive electrode active material is obviously enhanced, and under the same condition, the service life of the positive electrode current collector is prolonged. The stripping force of the positive electrode active material is obviously improved, so that the stability of the positive electrode active material on the foil surface is enhanced, the powder falling phenomenon in the circulation process is avoided, and the deformation resistance and the heat conductivity of the positive electrode current collector can be improved due to the existence of the copper-aluminum alloy, so that the electrical performance and the safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of current collector preparation, and in particular relates to a positive electrode current collector, a secondary battery and an electrical device. Background Art

[0002] Commercial lithium-ion batteries are a relatively popular and mature energy storage technology with high energy density, long life, and easy management. They are widely used in the power systems of new energy vehicles. However, due to the low global reserves of lithium resources, uneven distribution around the world, and the general positive electrode materials require the use of transition metals such as cobalt, this means that the raw materials of lithium-ion batteries have a relatively high cost. In comparison, sodium is stored in high concentrations around the world, has a low cost, and is applied to ion batteries with similar energy storage principles and process manufacturing methods as lithium-ion batteries. Therefore, it has regained attention in the new energy field in recent years.

[0003] Usually, sodium-ion batteries are composed of a positive electrode, a negative electrode, and a separator that are wound or stacked into a layered structure, which is then placed in a shell and injected with an electrolyte. As one of the main materials of the battery, the positive current collector is used to support the positive active material and transfer electrons between the active material and the external circuit. The positive active material is usually composed of active materials containing more sites, etc. Currently, it is mainly divided into three types of positive active materials: ternary materials, Prussian blue (white), and polyanion system materials. After adding different additives or binders, after stirring, dispersion and other processes, it is coated on a current collector such as aluminum foil for subsequent processes.

[0004] The bonding between the positive active material and the foil of the sodium-ion secondary battery is usually achieved through the interaction of interface forces and mechanical meshing forces. Interface forces include van der Waals forces and ionic bonds. The surface of the existing aluminum foil current collector is usually relatively smooth, and its bonding force with the positive active material is limited. When the coating weight is too high or the temperature is too high in the subsequent process, it will cause the pole piece to crack, resulting in micro-short circuits and safety issues. From the beginning of product design, it is necessary to limit the surface density of the positive active material, which affects the maximum amount of active material that can be carried. In addition, after multiple cycles, the sodium-ion secondary battery often suffers from reduced charge and discharge performance due to the peeling of the active material and the current collector, which may even cause micro-short circuits in severe cases, posing a safety hazard to subsequent thermal runaway and battery failure. Summary of the invention

[0005] Therefore, the present invention provides a positive electrode current collector, a secondary battery and an electrical device. On the one hand, the present invention solves the problem that the current collector in the prior art has limited bonding strength with the active material, and when the coating weight is too high or the temperature in the subsequent process is too high, the current collector cracks, causing micro short circuits. The product design needs to limit the surface density of the positive electrode material, which affects the maximum amount of active material that can be carried. On the other hand, the present invention solves the problem that after multiple cycles of the secondary battery, the active material and the current collector are peeled off, which reduces the charge and discharge performance, and even causes micro short circuits in severe cases, which bury safety hazards for subsequent thermal runaway and battery failure.

[0006] In order to solve the above technical problems, according to one aspect of the present invention, a positive electrode current collector is provided, comprising:

[0007] A body layer, wherein the material of the body layer includes aluminum;

[0008] A porous layer having a plurality of pore structures and disposed on at least one surface of the body layer;

[0009] The porous layer comprises a copper-aluminum alloy, and the average specific surface area of ​​the porous layer is 8 to 15 m 2 / g.

[0010] Furthermore, the average diameter of the pore structure in the porous layer is 50 nm to 6 μm.

[0011] Furthermore, the average depth of the pore structure in the porous layer is 100 nm to 4 μm.

[0012] Furthermore, the thickness of the porous layer is 150 nm to 4.5 μm.

[0013] Furthermore, the copper-aluminum alloy comprises CuAl 2 .

[0014] Furthermore, the thickness of the positive electrode current collector is 5 μm to 18 μm.

[0015] Furthermore, the porous layer further comprises single copper, and the content of single copper in the porous layer is 60wt% to 75wt%, CuAl 2 The content is 25 to 40 wt%.

[0016] Furthermore, the porosity of the porous layer is 30% to 50%.

[0017] In order to solve the above problem, according to one aspect of the present invention, a secondary battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises the above positive electrode current collector.

[0018] According to one aspect of the present invention, there is provided an electronic device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electronic device.

[0019] The technical solution of the present invention has the following advantages:

[0020] The present invention provides a positive electrode current collector, which includes a main body layer, the material of the main body layer includes aluminum; a porous layer, which has a plurality of pore structures and is arranged on at least one surface of the main body layer; the porous layer includes a copper-aluminum alloy, and the average specific surface area of ​​the porous layer is 8 to 15 m 2 / g. The present invention proposes a new aluminum foil current collector with a surface porous structure, wherein the porous layer comprises a copper-aluminum alloy and has an average specific surface area of ​​8 to 15 m 2 / g, can provide more attachment area, compared with the traditional smooth aluminum foil, it significantly enhances the bonding ability between the positive electrode current collector and the positive electrode active material. Under the same conditions, it significantly improves the peeling force of the positive electrode active material, thereby enhancing the stability of the positive electrode active material on the foil surface, avoiding the phenomenon of powder falling during the cycle process, and improving the electrical performance and safety performance of the battery. The porous layer contains copper-aluminum alloy, which can improve the deformation resistance and thermal conductivity of the positive electrode current collector, provide more options for the thermal conduction of the battery before the battery overheats and thermal runaway occurs, and slow down the thermal runaway. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 It is a schematic structural diagram of the positive electrode sheet obtained in Example 1 of the present invention;

[0023] Reference numerals:

[0024] 1- bulk layer; 2- porous layer; 3- positive electrode active material. DETAILED DESCRIPTION

[0025] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0026] As analyzed in the background technology, the prior art generally uses smooth aluminum foil as the positive electrode current collector, which has limited bonding strength with the positive electrode active material. Excessive coating weight or high temperature will cause the current collector to crack, resulting in micro-short circuits. The surface density of the positive electrode active material is limited from the beginning of product design, affecting the maximum performance of the total amount of positive electrode active material that can be carried. In addition, after multiple cycles, the secondary battery often has reduced charge and discharge performance due to the peeling of the positive electrode active material and the positive electrode current collector, which may even cause micro-short circuits, burying safety hazards for subsequent thermal runaway and battery failure. In order to solve these problems, the present invention provides a positive electrode current collector, a secondary battery and an electrical device.

[0027] In one embodiment of the present invention, there is provided a positive electrode current collector, comprising:

[0028] A body layer, wherein the material of the body layer includes aluminum;

[0029] A porous layer having a plurality of pore structures and disposed on at least one surface of the body layer;

[0030] The porous layer comprises a copper-aluminum alloy, and the average specific surface area of ​​the porous layer is 8 to 15 m 2 / g.

[0031] The surface of the positive electrode current collector of the present invention has a porous layer, and the average specific surface area of ​​the porous layer is 8 to 15 m 2 / g, which provides more attachment area for the positive electrode active material, significantly improves the bonding force between the positive electrode active material and the current collector, reduces the cracks between the positive electrode current collector and the positive electrode active material layer, and avoids the tendency of the current collector to crack due to cracks. Under the same conditions, the peeling force of the positive electrode active material layer can be significantly improved, thereby enhancing the stability of the positive electrode active material on the foil surface, so that the foil can bear more active material loads, avoiding the need to limit the surface density of the positive electrode material in the product design stage in the prior art, affecting the amount of active material that can be carried and the maximum performance, and reducing the problems of the positive electrode active material and the current collector peeling off after the battery has been cycled for many times, resulting in reduced charge and discharge performance or causing micro short circuits, thereby improving the electrical performance and safety performance of the battery. The porous layer contains copper-aluminum alloy. The copper element in the copper-aluminum alloy can provide better thermal conductivity, improve the thermal conductivity of the positive electrode collector, provide more options for the heat conduction direction of the battery cell before the battery overheats and thermal runaway occurs, and slow down the thermal runaway; the copper-aluminum alloy in the porous layer has a solid solution strengthening effect, which makes the tensile strength of the positive electrode collector of the present invention better, and makes the positive electrode collector have better deformation resistance.

[0032] Furthermore, the average specific surface area of ​​the porous layer of the present invention can be 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m2 / g, 8~11m 2 / g, 9~13m 2 / g, 10~14m 2 / g.

[0033] In some embodiments, the average diameter of the pore structure in the porous layer is 50 nm to 6 μm. For example, the average diameter of the pore structure is in the range of one or two of 100 nm, 200 nm, 500 nm, 1 μm, 3 μm, 5 μm, and 6 μm. This ensures that the electrode material slurry is stably combined with the porous structure and improves the peeling force of the active material layer.

[0034] In some embodiments, the average depth of the pore structure in the porous layer is 100 nm to 4 μm. For example, the average depth of the pore structure is one of 100 nm, 300 nm, 500 nm, 800 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 200 nm to 3.3 μm, 480 nm to 2.7 μm, and 950 nm to 1.8 μm. This can further ensure that the electrode material slurry is stably combined with the porous structure and improve the peeling force of the active material layer.

[0035] In some embodiments, the thickness of the porous layer is 150nm to 4.5μm. For example, the thickness of the porous layer is 150nm, 300nm, 500nm, 800nm, 1μm, 1.6μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 200nm to 3.3μm, 480nm to 2.8μm, 200nm to 900nm. In this way, the positive electrode current collector can have a suitable specific surface area while ensuring that the positive electrode current collector has a suitable rigidity.

[0036] In some embodiments, the copper-aluminum alloy comprises CuAl 2 .CuAl 2 It has a solid solution strengthening effect. The tensile strength of the copper-aluminum alloy is as high as 230-650MPa, the tensile strength of pure aluminum is 40-50MPa, and the tensile strength of commercial aluminum foil is 150-280MPa; the hardness of the copper-aluminum alloy is 80-150HB, and the hardness of the aluminum foil is 65-100HB. It can be seen that the tensile strength and hardness of the composite structure formed by the copper-aluminum alloy and the aluminum foil are higher than the aluminum foil used in the prior art, which effectively improves the mechanical properties of the positive electrode current collector. That is, the copper-aluminum alloy formed by the present invention can improve the deformation resistance of the positive electrode current collector.

[0037] In some embodiments, the porous layer further comprises single copper, and the content of single copper in the porous layer is 60wt% to 75wt%, CuAl 2The content is 25-40wt%. The thermal conductivity of copper is 398W / (m·K), which is much higher than the thermal conductivity of pure aluminum 247W / (m·K). The copper element has good thermal conductivity and can improve the thermal conductivity of the positive electrode collector. It provides more options for the thermal conduction direction of the battery before the battery overheats and thermal runaway occurs, thereby slowing down the thermal runaway. Furthermore, the content of elemental copper in the porous layer is one of 60wt%, 63wt%, 65wt%, 67wt%, 69wt%, 71wt%, 73wt% and 75wt%, CuAl 2 The content of is one of 25wt%, 28wt%, 30wt%, 32wt%, 35wt%, 38wt% and 40wt%.

[0038] In some embodiments, the thickness of the positive electrode current collector is 5 μm to 18 μm, which can ensure that the battery meets the design group margin requirements without reducing the mechanical properties of the positive electrode sheet.

[0039] In some embodiments, the porosity of the porous layer is 30% to 50%, which ensures that there are enough spaces on the surface of the current collector to accommodate the electrode slurry, ensures that the electrode material is tightly combined with the positive electrode current collector, and improves the peeling force.

[0040] In one embodiment of the present invention, a method for preparing a positive electrode current collector is provided, comprising the following steps:

[0041] (1) preheating the body; the material of the body includes aluminum foil;

[0042] (2) spraying molten copper onto at least one surface of the body by a spraying method;

[0043] (3) Dealloying treatment.

[0044] In some embodiments, in step (1), the thickness of the body is 3.5 μm to 15 μm; the temperature after preheating is 300° C. to 500° C., at which the splashing of copper droplets formed by molten copper during the spraying process in step (2) can be reduced.

[0045] In some embodiments, in step (2), the copper raw material is heated to 1090-1400° C. to obtain a copper metal molten liquid with good fluidity to form molten copper. During the spraying process, the average diameter of the copper droplets formed by the molten copper is controlled to be 100 nm-5 μm, and can be evenly distributed on the surface of the aluminum foil, so that the surface of the aluminum foil is melted and embedded in the aluminum foil.

[0046] In some embodiments, the step (2) further comprises a rolling step after the copper droplets solidify and the spraying is completed; the copper particles are embedded on the surface of the aluminum foil by utilizing the hardness characteristics of copper. It should be noted that before rolling, the temperature of the aluminum foil surface is 100°C to 500°C.

[0047] In some embodiments, after rolling, a heat treatment step is further included, wherein the heat treatment temperature is 200°C to 500°C and the time is 30min to 120min. The aluminum foil after rolling is heated to 200°C to 500°C for heat treatment, so that copper is alloyed on the surface of the aluminum foil to form a uniformly dispersed copper-aluminum alloy, wherein the copper-aluminum alloy phase includes copper, aluminum and a copper-aluminum alloy phase, wherein the copper-aluminum alloy phase includes a copper-based solid solution containing aluminum and an aluminum-copper alloy phase CuAl 2 , after 30min to 120min, an optimal solid phase diffusion distribution is achieved, and the thickness of the copper-aluminum alloy formed in this process is 200nm to 5μm.

[0048] In some embodiments, the step (3) further includes spray cleaning before the dealloying treatment; the cleaning liquid may be, but is not limited to, known solvents such as anhydrous ethanol and water.

[0049] In some embodiments, the step (3), the dealloying treatment includes chemically corroding the aluminum foil with an alkali solution and an acid solution in sequence to complete the dealloying treatment, and the copper-aluminum alloy after dealloying includes copper and a partial aluminum-copper alloy phase; after secondary cleaning, an aluminum foil having a nano-scale and / or micro-scale porous layer on the surface is obtained. It should be noted that aluminum foil is a common material in the art, and the present invention does not impose specific restrictions on this. The cleaning solution for the secondary cleaning can be, but is not limited to, a well-known solvent such as anhydrous ethanol.

[0050] In some embodiments, the alkali solution is preferably a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution, and the concentration of the alkali solution is 2.5 to 20 wt %.

[0051] In some embodiments, the acid solution is preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, and a phosphoric acid aqueous solution, and the concentration of the acid solution is 2.5 to 20 wt %.

[0052] In some embodiments, during the dealloying treatment, the temperature is 25° C. to 50° C. and the time is 5 min to 40 min.

[0053] The present invention uses a spraying method to evenly distribute molten copper on the surface of the aluminum foil, and solid-phase diffusion is performed through heat treatment to form copper, aluminum, and copper-aluminum alloy phases. After dealloying, part of the copper-aluminum alloy phase and elemental aluminum are removed, so that the aluminum foil surface forms a composite structure with uniform pore distribution and supported by solid aluminum foil, and no penetration is formed, thereby ensuring the stability of the aluminum foil. By using the preparation process of the present invention, while the porous layer of the present invention contains the copper-aluminum alloy phase and the copper element, the problem of a significant decrease in the mechanical properties of the aluminum foil due to the loss of alloy elements will not occur, and the bonding force between the aluminum foil and the positive electrode active material can also be improved. The main components of the aluminum foil surface after dealloying include copper and aluminum, which helps to control the morphology and pore size of the porous layer.

[0054] Furthermore, the method for preparing the positive electrode current collector provided by the present invention can omit the corona treatment step and simplify the process because the surface of the positive electrode current collector has a porous layer.

[0055] In one embodiment of the present invention, a secondary battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises the positive current collector. The secondary battery of the present invention comprises a sodium ion secondary battery, a lithium ion secondary battery, etc. Among them, the positive electrode plate comprises a positive current collector and a positive active layer disposed on at least one surface of the positive current collector, the positive active material layer comprises a positive active material, and the positive active material comprises at least one of a layered transition metal oxide, a polyanion type, and Prussian blue. They are not listed one by one here.

[0056] In one embodiment of the present invention, an electronic device is provided, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electronic device. In the field of electronic devices, the secondary battery can be used as an electrode material for supercapacitors, etc.

[0057] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0058] Example 1

[0059] This embodiment provides a method for preparing a positive electrode current collector, comprising the following steps:

[0060] Preheating treatment: Aluminum foil with a thickness of 8 μm is used, unwound by an unwinding mechanism, and preheated to 400° C. by a hot roller device.

[0061] Molten copper spraying treatment: The copper raw material is heated to 1200℃ to form molten copper, and then the molten copper is sprayed on the two surfaces of the aluminum foil in motion through a thermal spraying device. The average diameter of the molten copper droplets is 3μm (the diameter of the molten copper droplets can be obtained through an optical microscope test). After the average surface temperature of the aluminum foil drops to 400℃, the foil enters the heat treatment zone through a rolling device, the temperature is controlled at 400℃, and it continues to run in the zone for 30 minutes, forming a uniformly dispersed copper-aluminum alloy layer on the surface of the aluminum foil, and the average thickness of the copper-aluminum alloy layer is 4μm.

[0062] Dealloying treatment: After being rinsed with anhydrous ethanol and deionized water, the aluminum foil was immersed in a 5wt% NaOH solution for 5 minutes, and then immersed in a 2.5wt% HCl solution for 5 minutes to remove part of the copper-aluminum alloy phase and elemental aluminum. The dealloying temperature was 30°C. After being rinsed with anhydrous ethanol, a porous layer with several porous structures can be obtained on the surface of the aluminum foil, and the average pore size distribution can be controlled within 100nm. That is, a positive electrode current collector is obtained, and its structure is referenced Figure 1 The positive electrode current collector includes a main body layer 1 and a porous layer 2 arranged on the front and back surfaces of the main body layer. The material of the main body layer 1 includes aluminum, and the porous layer 2 includes a copper-aluminum alloy and copper alone.

[0063] This embodiment also provides a method for preparing a positive electrode sheet, the structure of which is shown in FIG. Figure 1 , comprising: mixing the positive electrode active material (specific compound is NaNi 0.4 Fe 0.4 Mn 0.2 O 2 ), conductive agent carbon nanotubes, and binder PVDF are mixed to obtain slurry, the slurry is coated on both sides of the above aluminum foil, and the positive electrode sheet is obtained after drying, rolling, cutting and other processes.

[0064] This embodiment also provides a method for preparing a battery, comprising:

[0065] Preparation method of negative electrode sheet: negative electrode active material (hard carbon), conductive agent carbon nanotubes, and binder sodium carboxymethyl cellulose are mixed in a mass ratio of 90:5:5, solvent water is added to obtain slurry, the slurry is coated on both sides of the current collector copper foil, and the negative electrode sheet is obtained after drying, rolling, cutting and other processes.

[0066] The positive electrode sheet, the separator (glass fiber separator), and the negative electrode sheet are stacked or wound in sequence, and the electrolyte (the electrolyte composition is 1M sodium salt NaPF 6 and ethylene carbonate and dimethyl carbonate in a molar ratio of 1:1), and assembled to obtain a battery.

[0067] Example 2-21

[0068] Embodiment 2-21 provides a positive electrode current collector, and the difference between the parameters of the positive electrode current collector and that of Embodiment 1 is shown in Table 1; the difference between the preparation methods of the positive electrode current collector is shown in Table 2. The preparation methods of the positive electrode sheet and the battery are the same as those of Embodiment 1.

[0069] Comparative Example 1

[0070] Comparative Example 1 provides a positive electrode current collector, the preparation process of which is as follows: an aluminum foil with a thickness of 12 μm is unwound by an unwinding mechanism and preheated to 400° C. by a hot roller device. (That is, the difference from Example 1 is that the preheated aluminum foil is not subjected to molten copper spraying and dealloying.) The preparation method of the positive electrode sheet and the battery is the same as that of Example 1.

[0071] Table 1 Parameters of positive electrode current collector provided in each embodiment and comparative example

[0072]

[0073]

[0074] Table 2 Process parameter adjustment of each embodiment and comparative example

[0075]

[0076] Test Case

[0077] The performance of the positive electrode current collector and the battery provided in each embodiment and comparative example was tested, as follows:

[0078] The test method for the tensile strength of the positive electrode current collector is as follows: a static tensile test is used. Under static conditions, the sample is loaded at a constant rate, and the strain and load data are measured to calculate the tensile strength of the material.

[0079] Test method for the hardness of the positive electrode current collector: Brinell hardness test method is adopted.

[0080] Peel force test method: disassemble the battery and use the peel test method to test the peel force between the positive electrode current collector and the active material layer.

[0081] Battery thermal safety performance test: The thermal safety performance of the batteries of the embodiment and comparative example was tested using the test method 8.1.5 in GB38031-2020 Safety requirements for power batteries for electric vehicles. The test passed if no thermal runaway occurred during the entire test process.

[0082] Cyclic performance test: Use 0.33C constant current to discharge the battery to the lower limit voltage of 1.5V, wait for 10 minutes, and charge it to the upper limit voltage of 4V at 1C constant current, and wait for 10 minutes. Repeat the above steps until the capacity retention rate is less than 80% relative to the first cycle capacity, then stop the test and record the total number of cycles.

[0083] Table 3 Test results of positive electrode current collector performance

[0084] Example tensile strength hardness Peel force Thermal safety test Cycle performance (cycle) Example 1 290Mpa 95HB 23N / m pass 1250 Example 2 290Mpa 96HB 20N / m pass 1500 Example 3 311MPa 105HB 18N / m pass 1300 Example 4 285MPa 95HB 22N / m pass 1600 Example 5 290Mpa 97HB 20N / m pass 1270 Example 6 295Mpa 100HB 20N / m pass 1600 Example 7 315MPa 110HB 22N / m pass 1400 Example 8 290Mpa 96HB 23N / m pass 1300 Example 9 290Mpa 93HB 22N / m pass 1450 Example 10 430MPa 120HB 21N / m pass 1280 Embodiment 11 320Mpa 95HB 20N / m pass 1300 Example 12 310MPa 98HB 19N / m pass 1450 Embodiment 13 300MPa 102HB 20N / m pass 1550 Embodiment 14 400MPa 122HB 25N / m pass 1200 Embodiment 15 290Mpa 95HB 24N / m pass 1350 Example 16 290Mpa 96HB 22N / m pass 1450 Embodiment 17 465Mpa 128HB 22N / m pass 1300 Embodiment 18 300MPa 98HB 23N / m pass 1400 Embodiment 19 290Mpa 102HB 21N / m pass 1260 Embodiment 20 295Mpa 96HB 22N / m pass 1250 Embodiment 21 290Mpa 95HB 21N / m pass 1400

[0085]

[0086] According to the above data, it can be seen that the positive electrode current collector of the present application can provide more adhesion area, and compared with the traditional smooth aluminum foil, the bonding ability between the positive electrode current collector and the positive electrode active material is significantly enhanced. Under the same conditions, the peeling force of the positive electrode active material is significantly improved, thereby enhancing the stability of the positive electrode active material on the foil surface and avoiding powder loss during the cycle process. In addition, the presence of copper-aluminum alloy can improve the deformation resistance and thermal conductivity of the positive electrode current collector, thereby improving the electrical performance and safety performance of the battery.

[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A positive electrode current collector, characterized in that: include: A body layer, wherein the material of the body layer includes aluminum; A porous layer having a plurality of pore structures and disposed on at least one surface of the body layer; The porous layer comprises a copper-aluminum alloy, and the average specific surface area of ​​the porous layer is 8 to 15 m 2 / g.

2. The positive electrode current collector according to claim 1, characterized in that: The average diameter of the pore structure in the porous layer is 50 nm to 6 μm.

3. The positive electrode current collector according to claim 1 or 2, characterized in that: The average depth of the pore structure in the porous layer is 100 nm to 4 μm.

4. The positive electrode current collector according to claim 1 or 2, characterized in that: The thickness of the porous layer is 150 nm to 4.5 μm.

5. The positive electrode current collector according to claim 1, characterized in that: The copper-aluminum alloy includes CuAl2.

6. The positive electrode current collector according to claim 1 or 2, characterized in that: The thickness of the positive electrode current collector is 5 μm to 18 μm.

7. The positive electrode current collector according to claim 1, characterized in that: The porous layer further comprises single-element copper, wherein the content of single-element copper in the porous layer is 60wt% to 75wt%, and the content of CuAl2 is 25 to 40wt%.

8. The positive electrode current collector according to claim 1, characterized in that: The porosity of the porous layer is 30% to 50%.

9. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode collector according to any one of claims 1 to 8.

10. An electronic device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electronic device.

Citation Information

Patent Citations

  • Flexible device and manufacturing method thereof

    CN105140525A

  • Electrode plate of secondary battery, secondary battery and preparation method of secondary battery

    CN113451586A

  • Positive current collector and preparation method thereof, positive plate and preparation method thereof, and battery

    CN114678533A

  • Current collector with porous surface and preparation method thereof

    CN116387526A

  • High-rate lithium ion battery, positive and negative pole pieces of high-rate lithium ion battery and preparation method of pole pieces

    CN116435458A